Vitamin D and gonadal function in men: a potential inverse U‐shaped association?. (16th March 2016) - Karras, S.; Anagnostis, P.; Kotsa, K.; Goulis, D. G.
Summary: Accumulating evidence from animal and human studies suggests that vitamin D, apart from its regulatory effects on musculoskeletal health, is involved in reproductive function in both genders. The basis of the interplay between vitamin D and reproduction lays on the presence of both vitamin D receptor (VDR) and 1α‐hydroxylase (CYP27B1) enzyme in reproductive organs. In males, VDR are present in testis, epididymis, prostate, and seminal vesicles. In Sertoli cells, whose secretory activities are ion channel‐dependent, vitamin D has been shown to stimulate calcium uptake through a nuclear receptor activity. Epidemiological studies support a positive association between serum 25‐hydroxy‐vitamin D [25(OH)D] concentrations and sperm motility in both fertile and infertile men In addition, large multi‐center, cross‐sectional studies from Europe and USA have shown positive, linear association between 25(OH)D and androgen concentrations. On the contrary, there are studies that support an inverse U‐shaped association, that is, men with both low and high 25(OH)D concentrations demonstrate poorer gonadal function compared with those with intermediate concentrations. Given the rapid increase in over‐the‐counter use of vitamin D supplements by men that anticipate advantageous health outcomes, the aim of the present commentary is to provide an overview of the studies that present either U‐shaped or linear association between 25(OH)D concentrations and male gonadal function.